2012
DOI: 10.1016/j.jacc.2012.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Eluting Balloon for Treatment of Superficial Femoral Artery In-Stent Restenosis

Abstract: The data suggest that adjunctive use of DEB for the treatment of SFA-ISR represents a potentially safe and effective therapeutic strategy. These data should be considered hypothesis-generating to design a randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
69
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(83 citation statements)
references
References 14 publications
12
69
1
1
Order By: Relevance
“…As much as the correlation between calcium and DEB performance appears clear, overall 12-month LLL of 0.61 ± 0.15 mm is similar to the results reported in other studies and obviously better than the LLL reported using conventional angioplasty [13][14][15][16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…As much as the correlation between calcium and DEB performance appears clear, overall 12-month LLL of 0.61 ± 0.15 mm is similar to the results reported in other studies and obviously better than the LLL reported using conventional angioplasty [13][14][15][16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 84%
“…In recent prospective studies, DEB have shown a primary patency at 1 year comprised between 83.7 [16] and 92.1 % [17]. Other studies comparing DEB versus PTA found a primary patency of DEB significantly higher compared with PTA: Tepe et al [14] reported a 6-month [15], who found in patients with femoropopliteal and infragenicular vascular disease a primary patency rate at 12 months of 76 % for DEB versus 39.6 % for the PTA arm (p = 0.04).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 However, for superficial femoral artery (SFA) ISR, currently available data are poor. In a small, prospective registry of DCBA for SFA ISR, 12,13 recurrent restenosis rates were 7.9% (4 of 39) and 29.7% (11 of 37) at 12 and 24 months, respectively. For diabetic patients, Liistro et al 14 reported significantly lower recurrent ISR rates at 12 months after DCBA compared with a historical POBA group (19.5% [8 of 41] …”
Section: Editorial See P 2198 Clinical Perspective On P 2236mentioning
confidence: 99%
“…The clinical study indicates that it is a secure and effective surgical method to treat restenosis in SFA. However, this led to cardiac failure in some cases and hence more studies may be necessary on patients with comorbidities [21]. In succession to angioplasty, stent implantation and bypass graft, other examination techniques can be used to follow up the patients' health condition.…”
Section: Introductionmentioning
confidence: 99%